Frontispiece: Mixed Allyl Rare‐Earth Borohydride Complexes: Synthesis, Structure, and Application in (Co‐)Polymerization Catalysis of Cyclic Esters. Issue 62 (7th November 2017) - Fadlallah, Sami; Jothieswaran, Jashvini; Capet, Frédéric; Bonnet, Fanny; Visseaux, Marc
Abstract : Such rare‐earth (RE) complexes (RE=La, Nd, Sm, Y, Sc) contain allyl and borohydride groups that are both potential initiators towards the ring‐opening polymerization of cyclic esters. They display high activity towards homo‐ and co‐polymerization ofl ‐LA and ϵ‐CL, producing a wide range of copolymers. The borohydride moiety is shown to preferentially initiate the polymerization. For more information see the Full Paper by F. Bonnet, M. Visseaux et al. onpage 15644 ff.